Synthesis of (E)-2-(4-Arylbut-1-en-3-ynyl)-4H-chromen-4-ones - Albuquerque, Hélio (2014)
Chromones are a well-known class of naturally occurring oxygencontaining heterocyclic compounds; many of them playing important biological functions in nature [1]. Although 2-methylchromones are one of the scarcest classes of natural chromones, their synthesis and reactivity is well studied. They can participate in several chemical transformations such as oxidation, thiation, hydrogenation, photolysis, cycloaddition and condensation reactions, being useful targets in the synthesis of novel heterocyclic compounds [2]. The acidity of the 2- methyl group, due to the low electron density at C-2 caused by oxygen atom and the α,β-unsaturated ketone system, led us to explore the condensation of 2-methylchromones [3] with propargyl aldehydes [4].